Educating Against Intellectual Vices - Clemente, Noel L. (Archīum Ateneo, 2024)
Intellectual character education has been primarily expressed in terms of educating for intellectual virtues (EFIV). This aim of teaching intellectual virtues has received some challenges, such as how it fails to articulate adequate action guidance through exemplarist pedagogy, and how it neglects the pervasiveness of intellectual vice among students. To respond to these challenges, this paper considers the aim of educating against intellectual vices (EAIV)–teaching students not to develop intellectual vices or weakening those that they have already developed–which comes with the emergence of vice epistemology. More specifically, I look at how negative epistemic exemplars can be used as a classroom strategy for EAIV, and demonstrate how this could address the aforementioned weaknesses of EFIV.